A Predictive Models for Advertisement Campaign Budget Allocation - Iqra kousar (Kashmir Journal of Science)
This study explores the role of predictive models in optimizing advertisement campaign budget allocation. As digital marketing grows more complex, predictive models offer data-driven insights that help advertisers allocate budgets more efficiently. These models use machine learning to analyze past performance, predict trends, and optimize resource distribution across channels, improving campaign outcomes and return on investment (ROI). Techniques such as real-time bidding (RTB), customer segmentation, and multi-touch attribution have enhanced budget allocation. However, challenges like data quality, model interpretability, and integration complexity limit widespread use. Predictive models are integrated into platforms like Google Ads and Facebook Ads Manager, optimizing cost-per-click (CPC) and conversion rates. Balancing automation with human oversight remains crucial. Research should focus on real-time data integration and ethical concerns around data privacy to ensure responsible use. Refining these models will empower advertisers to make better data-driven decisions, improving budget allocation and campaign success.